The wrong white crystals: not salt but sugar as aetiological in hypertension and cardiometabolic disease - DiNicolantonio, James J (Open Heart, 2014)
Cardiovascular disease is the leading cause of premature mortality in the developed world, and hypertension is its most important risk factor. Controlling hypertension is a major focus of public health initiatives, and dietary approaches have historically focused on sodium. While the potential benefits of sodium-reduction strategies are debatable, one fact about which there is little debate is that the predominant sources of sodium in the diet are industrially processed foods. Processed foods also happen to be generally high in added sugars, the consumption of which might be more strongly and directly associated with hypertension and cardiometabolic risk. Evidence from epidemiological studies and experimental trials in animals and humans suggests that added sugars, particularly fructose, may increase blood pressure and blood pressure variability, increase heart rate and myocardial oxygen demand, and contribute to inflammation, insulin resistance and broader metabolic dysfunction. Thus, while there is no argument that recommendations to reduce consumption of processed foods are highly appropriate and advisable, the arguments in this review are that the benefits of such recommendations might have less to do with sodium—minimally related to blood pressure and perhaps even inversely related to cardiovascular risk—and more to do with highly-refined carbohydrates. It is time for guideline committees to shift focus away from salt and focus greater attention to the likely more-consequential food additive: sugar. A reduction in the intake of added sugars, particularly fructose, and specifically in the quantities and context of industrially-manufactured consumables, would help not only curb hypertension rates, but might also help address broader problems related to cardiometabolic disease.